An HIV-1 gp120 Envelope Human Monoclonal Antibody That Recognizes a C1 Conformational Epitope Mediates Potent Antibody-Dependent Cellular Cytotoxicity (ADCC) Activity and Defines a Common ADCC Epitope in Human HIV-1 Serum - Ferrari, Guido (American Society for Microbiology, 2011)

(untitled)
Among nonneutralizing HIV-1 envelope antibodies (Abs), those capable of mediating antibody-dependent cellular cytotoxicity (ADCC) activity have been postulated to be important for control of HIV-1 infection. ADCC-mediating Ab must recognize HIV-1 antigens expressed on the membrane of infected cells and bind the Fcγ receptor (FcR) of the effector cell population. However, the precise targets of serum ADCC antibody are poorly characterized. The human monoclonal antibody (MAb) A32 is a nonneutralizing antibody isolated from an HIV-1 chronically infected person. We investigated the ability of MAb A32 to recognize HIV-1 envelope expressed on the surface of CD4(+) T cells infected with primary and laboratory-adapted strains of HIV-1, as well as its ability to mediate ADCC activity. The MAb A32 epitope was expressed on the surface of HIV-1-infected CD4(+) T cells earlier than the CD4-inducible (CD4i) epitope bound by MAb 17b and the gp120 carbohydrate epitope bound by MAb 2G12. Importantly, MAb A32 was a potent mediator of ADCC activity. Finally, an A32 Fab fragment blocked the majority of ADCC-mediating Ab activity in plasma of subjects chronically infected with HIV-1. These data demonstrate that the epitope defined by MAb A32 is a major target on gp120 for plasma ADCC activity.